TO TEACH: THE JOURNEY OF A TEACHER (3RD ED.) By William Ayers (New York: Teacher College Press, 2009) A Book Review - Sri Rejeki Murtiningsih (University of Muhammadiyah Purwokerto, 2012)
Why do we want to be teachers? It is a question that is commonly asked by a lot of peo-ple. William Ayers tries to look back on his moti-vation for being a teacher and attempts to answer the question. The challenges of being a teacher are revisited by looking at the misconceptions in teaching as well as providing the sensible argu-ments to explain the misunderstanding. To Teach: The Journey of A Teacher also challenges the teach-ers’ beliefs in viewing their students and in teach-ing practices in their classrooms. In addition, teachers are encouraged to be more proactive to embrace the policies rather than passively accept the mandated curriculum and other regulations enacted by the policy makers, administrators etc. This book presents a large number of classroom practices that are conducted in unconventional ways.